Uncovering transcriptomic landscape alterations of CAN-2409 in in vitro and in vivo glioma models - Koch, Marilin S.; Zdioruk, Mykola; Nowicki, Michal O.; Hoetker, Michael S.; Herbert, Zachary T.; Barone, Francesca; Tak, Paul P.; Chiocca, E. Antonio; Tabatabai, Ghazaleh; Lawler, Sean E. (Frontiers in Medicine, 2023)
Rationale: CAN-2409 is a locally delivered oncolytic therapy, which results in vaccination against the injected tumor. CAN-2409 consists of a non-replicating adenovirus armed with the Herpes virus thymidine kinase, which metabolizes ganciclovir into a phosphorylated nucleotide that is incorporated into the tumor cell’s genome, thereby inflicting immunogenic cancer cell death. While CAN-2409’s immunological impact has been well characterized, its effects on the tumor cells transcriptome remains unknown. We compared the transcriptomic landscape after treatment of glioblastoma models with CAN-2409 in vitro and in vivo to assess how the interplay with the tumor microenvironment influences CAN-2409-mediated transcriptome alterations. Methods: We performed RNA-Seq with CAN-2409 treated patient-derived glioma stem-like cells and tumors of C57/BL6 mice and compared KEGG pathway usage and differential gene expression focusing on immune cell and cytokine profiles. T-cell -killing assays were performed to assess candidate effectors. Results: PCA analysis showed distinct clustering of control and CAN-2409 samples under both conditions. KEGG pathway analysis revealed significant enrichment for p53 signaling and cell cycle pathway, with similar dynamics for key regulators of both pathways in vitro and in vivo, including MYC, CCNB1, PLK1 and CDC20. Cytokine expression analysis revealed upregulation of pro-inflammatory IL12a under both conditions; immune cell gene profiling showed reduction of myeloid associated genes. T-cell-killing assays showed increased killing in the presence of IL-12. Conclusion: CAN-2409 significantly alters the transcriptome both in vitro and in vivo. Comparison of pathway enrichment revealed mutual and differential utilization of pathways under both conditions, suggesting a modulating influence on the cell cycle in tumor cells, and of the tumor microenvironment on the transcriptome in vivo. IL-12 synthesis likely depends on interactions with the tumor microenvironment, and it facilitates CAN-2409 cell killing. This dataset provides potential to understand resistance mechanisms and identify potential biomarkers for future studies.